ANALISIS PENGARUH INDEKS PEMBANGUNAN MANUSIA, JUMLAH TENAGA KERJA, RASIO KETERGANTUNGAN DAN RASIO JENIS KELAMIN TERHADAP PERTUMBUHAN EKONOMI DI JAWA TENGAH TAHUN 2015-2021 - Avivah Isnaini; Sudati Nur Sarviah; Emma Dwi Ratnasari (Transpublika Publisher, 2023)
Economic growth is a long-term problem that is always faced by a country. Central Java Province is a province that has a low economic growth rate among other provinces on the island of Java. The purpose of this study is to see the effect of human development index, total labor, dependency ratio and sex ratio on economic growth in Central Java in 2015-2021. The analytical tool used is the Fixed Effect Model (FEM) panel data regression. The data used is secondary data from 35 districts / cities in Central Java. The results showed that the human development index, the number of workers and the sex ratio had a positive effect on economic growth in Central Java, while the dependency ratio had a negative effect on economic growth in Central Java.